High-impact-resistance building material suitable for lunar environment and used for lunar base construction, concrete, preparation method and application

By adding specific components such as light -burning MGO, heavy -fired MGO, phosphate and active Al2O3 to the moon base building materials, combined with dry mixing and wet mixing process, the stability and durability of existing materials in the vacuum environment are solved. It realizes the efficient hydration and impact resistance of materials.

CN119371177APending Publication Date: 2025-01-28JINLING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411474484.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing building materials for lunar bases have poor vacuum stability, poor thermal cycle durability, difficulty in hydration and impermissibility at low temperatures, which affect the construction of lunar bases.

Method used

Adopt a building material including light -burning MGO, heavy -fired MGO, phosphate, moon soil or simulation month soil, active AL2O3, fiber, graphene nano tablets, water absorption resin and water, and prepare through the steps of dry mixing and wet mixing Building building materials for lunar bases with strong impact.

Benefits of technology

The efficient hydration of materials in the moon environment, improving the impact resistance, improving the durability and denseness of the material, and meeting the building needs of the moon base.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-impact-resistance building material suitable for lunar environment and used for lunar base construction, concrete, a preparation method and application. The invention belongs to the technical field of aviation. The raw materials comprise light-burned MgO, dead-burned MgO, phosphate, lunar soil or simulated lunar soil, active Al2O3, fibers, graphene nanosheets, water-absorbent resin and water. A large amount of lunar soil can be used, the activity of the lunar soil can be stimulated, and the material for lunar base construction which is resistant to high temperature and low temperature, capable of being hydrated at the low temperature and excellent in impact resistance is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of aviation technology and relates to a building material for lunar base construction, and in particular to a building material and concrete for lunar base construction that is adaptable to the lunar environment and highly impact-resistant, as well as a preparation method and application. Background Art

[0002] The lunar base can not only be used as an energy development base, agricultural production base and space pharmaceutical base, but is also regarded as a "deep space transfer station". The construction of a lunar base is an important engineering requirement in today's lunar exploration mission, and it also faces technical difficulties. The building materials currently proposed for the lunar base have problems such as poor vacuum stability, poor thermal cycle durability, difficulty in hydration at low temperatures and low temperature resistance, which are not conducive to the construction of the lunar base. Therefore, the configuration of lunar concrete needs to consider a new type of cementitious material that can stimulate the activity of lunar soil, is resistant to high temperatures, resistant to low temperatures, has high thermal shock resistance, can be hydrated at low temperatures, and has high impact resistance.

[0003] Magnesium phosphate cement (MPC) is a good material with low water-cement ratio (as low as 0.1), hydration at -20℃, short setting time, high early strength, strong adaptability to ambient temperature, small deformation, wear resistance and frost resistance, etc. It is especially suitable for the unique environment of the moon. According to the analysis of the lunar soil samples obtained in the US "Apollo" series of missions, it is known that the main chemical components of the lunar soil are similar to those of fly ash (FA) and volcanic ash, and have higher activity.

[0004] Existing studies have shown that in addition to the active effect of volcanic ash in the MPC system, it also has an adsorption effect on phosphate ions. According to analysis, volcanic ash participates in the acid-base reaction of the MPC system to form K-struvite containing Si and Al elements and amorphous silicoaluminophosphate products. The silica-alumino glass in the volcanic ash reacts with phosphoric acid to produce a stronger phosphate-based cement material. CaO in the volcanic ash reacts with KH2PO4 to form calcium phosphate (Ca3(PO4)2). MgO reacts with KH2PO4 to form K-struvite, which ultimately changes the mechanical properties of MPC cement. Therefore, MPC stimulates the activity of lunar soil and effectively realizes the lunarization of the cementitious material components of the lunar base.

[0005] Currently, the more mature "simulated lunar soil" in the world include: the CAS series and CLRS series "simulated lunar soil" of the Chinese Academy of Sciences, the JLU series developed by Jilin University, the GVS and BH-1 series "simulated lunar soil" of the Beijing University of Aeronautics and Astronautics, the JSC-1, MLS-1, and MLS-2 "simulated lunar soil" of the United States, the MKS-1 and FJS-1 "simulated lunar soil" of Japan, and the SSC series "simulated lunar soil" of the United Kingdom.

[0006] The lunar environment is different from the ground environment. The high vacuum environment easily causes the rapid evaporation of the water used to mix lunar concrete. Therefore, this bottleneck problem needs to be considered when making lunar concrete. Reducing the evaporation of water in lunar concrete is a key technical indicator for preparing lunar concrete. Since there is no atmosphere to protect the moon, the lunar base will often be hit by meteoroids and meteorites. Therefore, when preparing lunar concrete, it must be ensured that it has extremely high impact resistance. The gravity on the lunar surface is only 1 / 6 of that on the earth, which can reduce the requirements for the compressive strength of building materials for the construction of lunar bases. Summary of the invention

[0007] The present invention provides a building material and concrete for lunar base construction that are adaptable to the lunar environment and highly impact-resistant, as well as a preparation method and application, so as to overcome the defects of the prior art.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] A building material for lunar base construction that is adaptable to the lunar environment and highly impact-resistant, comprising components: light-burned MgO, heavy-burned MgO, phosphate, lunar soil or "simulated lunar soil", active Al2O3, fiber, graphene nanosheets (GnP), water-absorbent resin and water.

[0010] To optimize the above technical solutions, the specific measures taken also include:

[0011] Furthermore, the sintering temperature of the light-burned MgO is 700-1000°C; the sintering temperature of the heavy-burned MgO is 1500-1700°C; the particle size of the light-burned MgO and heavy-burned MgO powders is 5-80 μm; the mass ratio of the light-burned MgO to the heavy-burned MgO is 1:9-30; the phosphate includes NH4H2PO4 and KH2PO4; the mass ratio of NH4H2PO4 to KH2PO4 is 1-3:1; in order to ensure the complete reaction of the phosphate and reduce the "white frost" phenomenon on the surface of the material, the phosphate needs to be dried in a 60°C oven in advance, and then the cooled phosphate is placed in a ball mill and ball-milled to a fineness of 0.080 mm and a sieve residue rate of less than 10%; the light-burned MgO and heavy-burned MgO powders are ...:1 The ratio of the total molar mass of burnt MgO to the molar mass of phosphate is 4-10:1; the "simulated lunar soil" is the JLU-2 type "simulated lunar soil" prepared by Jilin University with the black-gray volcanic slag of Gushan in Jinchuan Town, Huinan County, Jilin Province as raw materials, the CAS series, CLRS series of the Chinese Academy of Sciences, the GVS and BH-1 series "simulated lunar soil" of Beijing University of Aeronautics and Astronautics, the JSC-1, MLS-1, MLS-2 "simulated lunar soil" of the United States, the MKS-1 and FJS-1 "simulated lunar soil" of Japan or the SSC series "simulated lunar soil" of the United Kingdom; the dosage of lunar soil or "simulated lunar soil" is 30-60% of the total mass of light-burned MgO, heavy-burned MgO and phosphate (i.e., MPC).

[0012] Furthermore, it also includes a retarder; the retarder is one or more of borax, boric acid, sodium chloride, and sodium tripolyphosphate; the amount of the retarder is 0 to 10% of the total mass of light-burned MgO and heavy-burned MgO.

[0013] Furthermore, the sintering temperature of the active Al2O3 is 1000-1200°C; the dosage of the active Al2O3 is 5-20% of the total mass of the light-burned MgO and the heavy-burned MgO.

[0014] Furthermore, the fiber is glass fiber or polyethylene fiber; the fiber content is 0.5-3% of the total volume of all components; the fiber length is 6 mm, the diameter is 5-8 μm, the density is 2.5-2.7 g / cm3, the elastic modulus is 60-100 GPa, and the tensile strength is 1800-3000 MPa.

[0015] Furthermore, the addition amount of the graphene nanosheet is 0.15-0.25% of the total mass of the light-burned MgO and the heavy-burned MgO; the graphene nanosheet is formed by stacking graphene sheets with a plate-like morphology, and the density is 2.2g / cm 3 The average thickness is about 6-8nm, and the specific surface area is 120-150m 2 / g, with an average particle size of 50μm; the water-absorbent resin is a polyacrylic acid-based superabsorbent polymer (SAP); and the amount of the water-absorbent resin is 0.3-2.0% of the total mass of the light-burned MgO and the heavy-burned MgO.

[0016] Furthermore, the water is added in a solid slushy state; the water-to-binder ratio is 0.10 to 0.30.

[0017] The present invention also provides a kind of concrete which is adaptable to the lunar environment and has strong impact resistance, and is made of the above-mentioned building materials for the construction of the lunar base.

[0018] The present invention also provides a method for preparing the above-mentioned concrete that is adapted to the lunar environment and has strong impact resistance, comprising the following steps: S1, dry mixing: in a vacuum environment, light-burned MgO, heavy-burned MgO, phosphate, retarder, lunar soil or "simulated lunar soil", and graphene nanosheets are dry mixed until all powder materials are mixed evenly to ensure that there is no obvious lumps or separation; S2, wet mixing: gradually add ice cream and water-absorbent resin to the dry-mixed powder material, and continue mixing until the mixing is uniform; S3, fiber addition: gradually add fiber during the stirring process until the mixing is uniform to obtain concrete material; S4, concrete molding: pour the evenly mixed concrete material into a mold and vibrate it into shape; the mold is selected according to the design requirements of the concrete structure. The compaction treatment is specifically: using an appropriate method (such as a vibration table) to compact the concrete to ensure that there are no bubbles inside the concrete to improve its density and mechanical properties; S5, maintenance and demolding.

[0019] The present invention also provides the application of the above-mentioned building materials and concrete for lunar base construction in the field of lunar base.

[0020] Taking into account the high vacuum, low gravity, and many meteorites environment of the moon, the present invention proposes a new type of lunar base construction material (RLMPC) that is adapted to the lunar vacuum environment, can stimulate the activity of lunar soil, can be hydrated at low temperatures, has fast coagulation and hardening, and is impact-resistant. In this material, the MPC prepared from MgO and phosphate is used as a cementitious material, and the lunar soil is used as a fine aggregate. The use of local lunar soil can reduce the cost of lunar base construction. The addition of fibers can improve the impact resistance of the material and improve its brittleness. The addition of active Al2O3 can effectively increase the hardness of the material and improve its impact resistance. The high elastic modulus of graphene nanosheets helps to improve the crack resistance of the material and reduce the formation of cracks. The water-absorbent resin can reduce the evaporation of water in a high vacuum environment.

[0021] The beneficial effects of the present invention are:

[0022] 1. The active Al2O3 and graphene nanosheets added in the present invention optimize the setting time of MPC cement and greatly improve the strength of magnesium phosphate cement.

[0023] Second, the fiber significantly improves the impact resistance of RLMPC materials and improves the disadvantage of MPC cement's excessive brittleness.

[0024] 3. Adding SAP to RLMPC can reduce the evaporation of water from the material on the moon and improve the workability of the material.

[0025] Fourth, the aluminosilicate glass phase of the lunar soil or "simulated lunar soil" dissolves inside the pH-neutral MPC hydration product and generates silicon-aluminum phase substances, thereby improving the density and durability of the matrix. Therefore, the lunar soil or "simulated lunar soil" in the present invention is not only the aggregate of the lunar base concrete, but also the activity of the lunar soil or "simulated lunar soil" can be stimulated by MPC. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a flow chart of concrete preparation and impact resistance testing;

[0027] Figure 2 is the particle size distribution diagram of MgO;

[0028] Figure 3 It is the particle size range and morphology of the "simulated lunar soil", where a is the particle size distribution curve of the "simulated lunar soil" and b is the SEM image of the "simulated lunar soil";

[0029] Figure 4 This is a diagram of the atomic structure of a graphene nanosheet;

[0030] Figure 5 are photos of the compressive failure phenomenon of the lunar concrete prepared in each embodiment, wherein a is a photo of the compressive failure phenomenon of a cube, and b is a photo of the compressive failure phenomenon of a cylinder;

[0031] Figure 6 It is the standard waveform for impact compression test;

[0032] Figure 7 is the stress balance diagram of the impact compression test;

[0033] Figure 8 It is a plastic piece for impact compression test;

[0034] Fig. 9 It is the MPC quasi-static stress-strain curve;

[0035] Fig.10 It is the failure morphology diagram of RLMPC specimens with different fibers added at different strain rates;

[0036] Fig.11 It is the impact compression stress-strain curve of RLMPC with different materials. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with specific embodiments.

[0038] Embodiments 1 to 4

[0039] This embodiment provides a lunar concrete made of lunar base construction building materials (RLMPC), and the preparation method is as follows: Figure 1As shown in Table 1, weigh each raw material, put light-burned MgO, heavy-burned MgO, phosphate (KH2PO4 (KDP) and NH4H2PO4 (ADP)), retarder, "simulated lunar soil", active Al2O3, and graphene nanosheets into a blender and slowly dry mix for 30 seconds. After mixing evenly, add ice and absorbent resin polyacrylic acid-based superabsorbent polymer and stir slowly for 30 seconds, then stir quickly for 30 seconds. Then add fiber (glass fiber or polyethylene fiber, no fiber is added in Example 1) and stir quickly for 100 seconds to obtain a concrete material. The concrete material is quickly poured into a mold and vibrated. After forming, it is quickly placed in a vacuum curing box for curing and demolding. The condensation environment simulates the vacuum environment of the moon, which is helpful for subsequent testing of the performance of the concrete.

[0040] Table 1 RLMPC components and ratios of various examples

[0041]

[0042] In the table, MPC represents the mass fraction of each component, VA represents the percentage of "simulated lunar soil" in the total mass of MPC, W / C is the water-to-cement ratio, GF and PF represent the percentage of glass fiber and polyethylene fiber in the total volume of all components, GnP represents the percentage of graphene nanosheets in the total mass of MgO, active Al2O3 represents its percentage in the total mass of MgO, and SAP is the percentage of polyacrylic acid-based superabsorbent polymer in the total mass of MgO.

[0043] Among them, light-burned MgO and heavy-burned MgO are both industrial grade, from Dashiqiao, Liaoning, and are prepared by calcining magnesite. The calcination temperatures of light-burned MgO and heavy-burned MgO are 700℃ and 1700℃ respectively. The coarseness of MgO is 200 mesh, and its particle size distribution is measured by a laser particle size analyzer. Figure 2 As shown. According to the hydration method, the activities of light-burned and heavy-burned MgO are 65.34% and 15.01% respectively. Table 2 shows the main chemical components of MgO measured by X-ray fluorescence analysis (XRF).

[0044] Table 2 Chemical composition of MgO

[0045] Element MgO <![CDATA[Fe2O3]]> CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[TiO2]]> MnO <![CDATA[P2O5]]> LOI content / % 79.37 10.30 5.00 3.14 0.80 0.15 0.79 0.09 0.36

[0046] Note: LOI is loss on ignition.

[0047] The "simulated lunar soil" is a JLU series "simulated lunar soil" developed by the Key Laboratory of Engineering Bionics of the Ministry of Education of Jilin University. The initial material is the volcanic ash of the Huinan Cenozoic volcano in Jilin Province. The particle size range and morphology of the particles are as follows Figure 3 shown.

[0048] The atomic structure of graphene nanosheets is as follows Figure 4As shown. Graphene nanosheets are stacked with plate-like graphene sheets and have a density of 2.2 g / cm 3 The average thickness is about 6-8nm, and the specific surface area is 120-150m 2 / g, and the average particle size is 50μm.

[0049] The two ends of the demoulding specimen are ground flat, and then the impact resistance test is performed using a Hopkinson bar. In order to ensure the uniformity of the dynamic impact test, the parallelism tolerance of the specimen surface is controlled within 0.05 mm. Before the test, the specimen is carefully polished using a grinder. The specific grinding steps are as follows: First, fix the specimen on the fixture, adjust the height of the grinding disc so that it contacts the upper surface of the specimen and then resets. Then start the grinder and connect the water injection pipe, rotate the grinder to move the grinding disc back and forth on the surface of the specimen. There are two purposes of water injection: one is to wash away the debris and concrete powder generated during the grinding process; the other is to reduce the temperature of the specimen and the grinding disc to prevent excessive temperature from affecting the performance of the specimen. In order to meet the parallelism requirements, both end faces of the specimen need to be polished.

[0050] The dimensions of the molded specimens are as follows:

[0051] Table 3 Specimen shape, size, quantity and performance test

[0052] shape Dimensions (mm) quantity test cube 100×100×100 3 Cube Compression Cylinder Φ75×37.5 18 Shock Compression Cylinder Φ75×75 3 Cylinder compression resistance

[0053] The setting time, cube compressive strength, cylinder compressive strength and dynamic compression performance of each embodiment were tested. The setting time is shown in Table 1, the cube compressive strength and cylinder compressive strength are shown in Table 4, and the compressive failure phenomenon is shown in the following photos. Figure 5 shown.

[0054] Table 4 Static compressive strength of concrete in each embodiment

[0055] serial number Cube static compressive strength / MPa Static compressive strength of cylinder / MPa 0F-RLMPC 8.2 7.3 GF-RLMPC-1 15.1 10.8 GF-RLMPC-2 12.0 8.5 PF-RLMPC 10.5 6.2

[0056] Table 4 shows that from the analysis of cube compressive strength, adding different fibers with the same volume fraction (1.5%) has different effects on the compressive strength of RLMPC. The compressive strength of OF-RLMPC without fiber is 8.2MPa. After adding GF, the compressive strength of GF-RLMPC-1 is 15.1MPa, which is 84.1% higher than that of OF-RLMPC. After adding PF, the compressive strength of PF-RLMPC is 10.5MPa, which is 28.0% higher than that of OF-RLMPC. The addition of graphene nanosheets and active Al2O3 has an effect on the compressive strength of RLMPC. The compressive strength of GF-RLMPC-2 without graphene nanosheets and active Al2O3 is 12.0MPa, and the compressive strength of GF-RLMPC-1 with graphene nanosheets and active Al2O3 is 15.1MPa, which is 25.8% higher than that of GF-RLMPC-2. The order of cube compressive strength from high to low is: GF-RLMPC-1>GF-RLMPC-2>PF-RLMPC>0F-RLMPC. Glass fiber (GF) and polyvinyl alcohol fiber (PF) have an enhancing effect on the compressive strength of RLMPC. GF-RLMPC-1 is 84.1% higher than that of 0F-RLMPC. Glass fiber provides additional reinforcement in the MPC matrix. The bonding force between the fiber and the matrix can effectively transfer stress, thereby improving the overall compressive strength. PF-RLMPC is 28.0% higher than 0F-RLMPC. PF has good toughness and ductility, and can absorb and disperse energy when subjected to stress, reducing brittle fracture and thus improving compressive strength.

[0057] From the analysis of the compressive strength of the cylinder, the addition of different fibers with the same volume fraction (1.5%) has different effects on the compressive strength of RLMPC. The compressive strength of OF-RLMPC without fiber is 7.3MPa; the compressive strength of GF-RLMPC-1 after adding GF is 10.8MPa, which is 47.9% higher than that of OF-RLMPC; the compressive strength of PF-RLMPC after adding PF is 6.2MPa, which is 15.1% lower than that of OF-RLMPC. The addition of graphene nanosheets and active Al2O3 has an effect on the compressive strength of RLMPC. The compressive strength of GF-RLMPC-2 without graphene nanosheets and active Al2O3 is 8.5MPa, and the compressive strength of GF-RLMPC-1 with graphene nanosheets and active Al2O3 is 10.8MPa, which is 23.2% higher than that of GF-RLMPC-2. The order of cylinder compressive strength from high to low is: GF-RLMPC-1>GF-RLMPC-2>0F-RLMPC>PF-RLMPC.

[0058] The working performance of RLMPC after adding additives was tested: after adding fiber, the coagulation time of RLMPC could be prolonged, among which GF prolonged the coagulation time of RLMPC by 14.2%. The addition of GnP, active Al2O3 and SAP had different effects on the fluidity of RLMPC. After adding GnP and active Al2O3, the fluidity of RLMPC increased by 1.4%, and after adding SAP, the fluidity of RLMPC increased by 5.1%.

[0059] The impact compression test was conducted on the lunar concrete of each embodiment: (1) Preparation before the test: Carefully check whether the bullet, incident rod, transmission rod and the strain gauges attached to them are damaged; confirm whether the gas pressure in the nitrogen bottle reaches the required level; verify whether the data acquisition system can accurately capture the required data. (2) Preload test: Perform the SHPB test without placing the test piece to check whether the waveforms of the incident wave and the transmission wave are normal to ensure the accuracy of the waveforms, such as Figure 6 As shown, the stress uniformity assumption of the specimen is verified to ensure the validity of the test data. The verification results are shown in Figure 7 (3) Formal loading: Before the experiment begins, a plastic sheet needs to be attached to the end face of the incident rod near the bullet, as shown in Figure 8 As shown. The selection of the shaping piece should meet two criteria: first, the shaping piece can convert the rectangular waveform into a half-sine wave, thereby generating a stress peak; second, the time of the rising edge of the waveform should be long enough so that the specimen can obtain a long loading time to verify the assumption of stress uniformity of the specimen. In this experiment, the shaping piece used is made of rubber, with a diameter of 25 mm and a thickness of 2 mm. The specimen should be clamped between the incident rod and the transmission rod, and vaseline should be applied on the fitting surface to ensure full contact. Next, open the high-pressure gas cylinder, fill the launch device with nitrogen, and control the speed of the bullet by adjusting the gas pressure to obtain different strain rates. After all preparations are completed, set the DHDAS dynamic signal acquisition and analysis system to the acquisition mode, and then open the air valve to launch the bullet. (4) Data acquisition and processing: The pulse signals collected by the strain gauges installed on the incident rod and the transmission rod are analyzed and processed by the data acquisition system, which is responsible for converting the collected signals into corresponding engineering stress, engineering strain and engineering strain rate curves. (5) End of the test: The failure morphology of the specimen after impact is retained and photographed for preservation. RLMPC impact compression mechanical parameters include peak stress, peak strain and dynamic growth factor (DIF) after impact. MPC quasi-static stress-strain curve is shown in Fig. 9 The quasi-static mechanical parameters of RLMPC are shown in Table 5.

[0060] Table 5 RLMPC quasi-static mechanical parameters of each embodiment

[0061] serial number <![CDATA[Axial compressive strength f pr / MPa]]> <![CDATA[Peak strain ε pr / 10 -3 > <![CDATA[Elastic modulus E c / GPa]]> 0F-RLMPC 5.94 1.34 3.5 GF-RLMPC-1 8.74 2.59 5.8 GF-RLMPC-2 7.02 1.88 4.4 PF-RLMPC 4.66 1.17 3.0

[0062] Analysis of the uniaxial stress-strain curve of RLMPC shows the following rules: under the action of static compression load, with the addition of different fibers, the elastic modulus of the RLMPC specimen decreases significantly; and the addition of different fibers improves the quasi-static compressive strength and deformation capacity of RLMPC. Among them, the RLMPC mixed with GF has the highest enhanced compressive strength and deformation capacity, which are increased by 0.71 times and 2.64 times respectively, indicating that GF plays a role in reducing brittleness and increasing toughness under quasi-static uniaxial compression.

[0063] From the impact compression stress-strain curves under different strain rates, it can be seen that as the strain rate increases, the peak stress, peak strain and elastic modulus of the RLMPC specimen increase. This phenomenon shows that RLMPC is a strain rate hardening material with obvious strain rate effect.

[0064] The failure morphologies of RLMPC specimens with different fibers at different strain rates are shown in Figure 2. Fig.10 As shown. From these failure modes, the failure modes of each group are that the degree of fragmentation continues to increase with the continuous increase of strain rate, and can be roughly divided into the following four failure states: (1) Undamaged state: When the specimen is impacted at a lower strain rate, the tensile stress inside the concrete is less than the stress required for the internal microcracks to expand. At this time, the specimen remains intact and there are no obvious cracks on the surface. (2) Initial cracking failure state: As the strain rate gradually increases, a few cracks appear on the surface of the specimen, and a few fragments fall off the edge of the specimen. (3) Overall cracking failure state: When the strain rate continues to increase, the number of cracks and fragments of the specimen increases, and the cracks penetrate the specimen axially to form many columnar fragments. At this time, the specimen is overall cracked. (4) Crushing failure state: When the strain rate increases to a certain level, the specimen is split into columnar fragments, and the larger impact load presses the specimen into very small fragments. At this time, the specimen is crushed.

[0065] At high strain rates, that is, when the strain rate exceeds 100s -1 When the GF-RLMPC was subjected to high strain rate, it only reached the initial cracking failure state, while the PF-doped RLMPC reached the crushing failure state. This phenomenon shows that under high strain rate environment, GF can effectively improve the impact resistance of RLMPC, making the material failure morphology manifest as ductile failure. This enhancement effect helps to improve the toughness of RLMPC during dynamic impact compression. After adding graphene nanosheets, active Al2O3 and water-absorbent resin, the toughness of RLMPC is enhanced to a certain extent and the impact resistance is improved.

[0066] The impact compression stress-strain curves of RLMPC with different materials are shown in Fig.11As shown in Table 6, the strain rate is controlled between 15s-1 and 150s-1, and the dynamic mechanical properties parameters corresponding to each set of curves are shown in Table 6.

[0067] Table 6 Impact compression mechanical parameters of RLMPC

[0068]

[0069]

[0070] In Examples 1 to 4, the cylindrical impact strength, cubic compressive strength and cylindrical compressive strength of Example 2 (GF-RLMPC-1) are 8.74 MPa, 15.1 MPa and 10.8 MPa, respectively, which are higher than those of other examples, indicating that the addition of GF, GnP, active Al2O3 and SAP can effectively improve the impact resistance of RLMPC.

[0071] The performance test data of the impact-resistant concrete of Examples 2 to 3 show that the impact strength, cube compressive strength and cylindrical compressive strength of the concrete obtained in Examples 2 to 3 are 7.02M to 8.74MPa, 12.0 to 15.1MPa and 8.5 to 10.8MPa, respectively, which are higher than those in Example 1 and Example 4. This shows that adding GF is more appropriate and improves the impact resistance of concrete. This is because GF can effectively improve the strength and toughness of RLMPC, so that RLMPC exhibits excellent performance under both static compression and dynamic impact. The high elastic modulus of GnP and the water absorption performance of SAP respectively improve the crack resistance and workability of the material, which can effectively prevent the generation and expansion of concrete cracks, thereby improving the impact resistance of concrete.

[0072] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields.

[0073] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A building material for lunar base construction that is adaptable to the lunar environment and has strong impact resistance, characterized in that: The components include: light-burned MgO, heavy-burned MgO, phosphate, lunar soil or "simulated lunar soil", active Al2O3, fiber, graphene nanosheets, absorbent resin and water.

2. The building material for lunar base construction that is adapted to the lunar environment and has strong impact resistance according to claim 1 is characterized in that: The sintering temperature of the light-burned MgO is 700-1000°C; the sintering temperature of the dead-burned MgO is 1500-1700°C; the particle size of the light-burned MgO and dead-burned MgO powders is 5-80 μm; the mass ratio of the light-burned MgO to the dead-burned MgO is 1:9-30; Phosphates include NH4H2PO4 and KH2PO4; the mass ratio of NH4H2PO4 to KH2PO4 is 1 to 3:1; The ratio of the total molar mass of light-burned MgO and heavy-burned MgO to the molar mass of phosphate is 4 to 10:1; The dosage of lunar soil or "simulated lunar soil" is 30-60% of the total mass of light-burned MgO, heavy-burned MgO and phosphate.

3. The building material for lunar base construction that is adapted to the lunar environment and has strong impact resistance according to claim 1 is characterized in that: It also includes retarders; The retarder is one or more of borax, boric acid, sodium chloride and sodium tripolyphosphate; The amount of retarder added is 0 to 10% of the total mass of light-burned MgO and heavy-burned MgO.

4. The building material for lunar base construction that is adaptable to the lunar environment and has strong impact resistance according to claim 1 is characterized in that: The sintering temperature of the active Al2O3 is 1000-1200°C; The amount of active Al2O3 added is 5-20% of the total mass of light-burned MgO and heavy-burned MgO.

5. The building material for lunar base construction that is adaptable to the lunar environment and has strong impact resistance according to claim 1 is characterized in that: The fiber is glass fiber or polyethylene fiber; The fiber content is 0.5-3% of the total volume of all components; The fiber length is 6 mm, the diameter is 5-8 μm, and the density is 2.5-2.7 g / cm 3 , elastic modulus is 60~100GPa, and tensile strength is 1800~3000MPa.

6. The building material for lunar base construction that is adaptable to the lunar environment and has strong impact resistance according to claim 1 is characterized in that: The addition amount of the graphene nanosheets is 0.15-0.25% of the total mass of the light-burned MgO and the heavy-burned MgO; The water-absorbent resin is a polyacrylic acid-based highly water-absorbent polymer; The amount of the water-absorbing resin added is 0.3-2.0% of the total mass of the light-burned MgO and the heavy-burned MgO.

7. The building material for lunar base construction that is adaptable to the lunar environment and has strong impact resistance according to claim 1 is characterized by: The water is added in a solid smoothie state; The water-to-cement ratio is 0.10-0.

30.

8. A concrete that is adapted to the lunar environment and has strong impact resistance, characterized in that: Made of the building material for lunar base construction as described in any one of claims 1 to 7.

9. The method for preparing the concrete adapted to the lunar environment and having strong impact resistance as claimed in claim 8, characterized in that: The following steps are involved: S1. In a vacuum environment, light-burned MgO, heavy-burned MgO, phosphate, retarder, lunar soil or "simulated lunar soil", and graphene nanosheets are dry-mixed until all powder materials are evenly mixed; S2. Gradually add the ice smoothie and water-absorbing resin to the dry-mixed powder material, and continue to mix until the mixture is uniform; S3, gradually adding fibers during the mixing process until the mixture is uniformly mixed to obtain a concrete material; S4, pouring the evenly mixed concrete material into a mold and vibrating and shaping it; S5, curing and demoulding.

10. Use of the building material for lunar base construction according to any one of claims 1 to 7 or the concrete according to claim 8 in the field of lunar base.